Milk fat globule membrane supplementation in formula modulates the gut microbiome and metabolic status of piglets and normalizes intestinal development - Zhou, Zonghan; Liu, Bin; Shen, Jun; Yan, Caihong; Yang, Guang; Zhang, Yu; Zhao, Junying; Chen, Lijun (Frontiers in Nutrition, 2025)
Milk fat globule membrane (MFGM) supplementation of infant formula demonstrates potential efficacy in modulating gut microbiota and metabolic profiles. However, the associated site-specific effects on intestinal microbial composition remain unclear. In this study, we used a neonatal piglet model to investigate the mechanisms associated with the metabolic regulation of supplemental MFGM and characterized the compartment-specific modulatory effects on intestinal microbial communities. A total of 20 piglets were randomly allotted to one of the following three groups: breastfed (BF), standard formula (SF), and MFGM-supplemented formula (EF). These diets were administered until weaning, with subsequent provision of commercial feed until euthanasia. Morphometric, microbial, and serum metabolomic analyses revealed that compared to piglets in the SF group, those in the EF group were characterized by significantly enhanced jejunal villus height (p < 0.05) and reduced cecal Oxalobacter (p < 0.05) and Pasteurella abundances, which were comparable to the levels detected in the BF group. Metabolically, piglets in the SF group demonstrated significantly lower levels of tyrosine, phenylalanine, and β-alanine (p < 0.05) and higher levels of 3-methyl-2-oxovalerate (p < 0.05) than those in BF piglets. In contrast, compared to the SF piglets, EF piglets exhibited significantly elevated levels of betaine (p < 0.05) and lysine. Spearman’s correlation analysis revealed significant positive associations between Oxalobacter abundance and creatinine, dimethyl sulfone, phenylalanine, tyrosine, and β-alanine concentrations, with inverse correlations observed for 3-methyl-2-oxovalerate and lysine levels. In conclusion, these findings revealed that MFGM supplementation contributes to maintaining a normal intestinal architecture, modulates site-specific microbiota, and mitigates metabolic disparities between formula-fed and breastfed neonates. Notably, these effects are primarily mediated via choline pathway regulation and competitive inhibition of pathogenic bacteria.